Design of chitosan colon delivery micro/nano particles for an Achillea millefolium extract with antiproliferative activity against colorectal cancer cells - María de las Nieves Siles-Sánchez; Irene Fernández-Jalao; Laura Jaime De Pablo; Susana Santoyo (Taylor & Francis Group, 2024)
In this study, chitosan low molecular weight (LCH) and chitosan medium molecular weight (MCH) were employed to encapsulate a yarrow extract rich in chlorogenic acid and dicaffeoylquinic acids (DCQAs) that showed antiproliferative activity against colon adenocarcinoma cells. The design of CH micro/nanoparticles to increase the extract colon delivery was carried out by using two different techniques: ionic gelation and spray drying. Ionic gelation nanoparticles obtained were smaller and presented higher yields values than spray-drying microparticles, but spray-drying microparticles showed the best performance in terms of encapsulation efficiency (EE) (> 94%), also allowing the inclusion of a higher quantity of extract. Spray-drying microparticles designed using LCH with an LCH:extract ratio of 6:1 (1.25 mg/mL) showed a mean diameter of 1.31 ± 0.21 µm and EE values > 93%, for all phenolic compounds studied. The release profile of phenolic compounds included in this formulation, at gastrointestinal pHs (2 and 7.4), showed for most of them a small initial release, followed by an increase at 1 h, with a constant release up to 3 h. Chlorogenic acid presented the higher release values at 3 h (56.91% at pH 2; 44.45% at pH 7.4). DCQAs release at 3 h ranged between 9.01- 40.73%, being higher for 1,5- and 3,4-DCQAs. After gastrointestinal digestion, 67.65% of chlorogenic and most DCQAs remained encapsulated. Therefore, spray-drying microparticles can be proposed as a promising vehicle to increase the colon delivery of yarrow phenolics compounds (mainly chlorogenic acid and DCQAs) previously described as potential agents against colorectal cancer.